Analisis Life Cycle Assessment (LCA) Pada Sistem Pengolahan Air Limbah Berbasis Moving Bed Biofilm Reactor (MBBR) Menggunakan Openlca - Bheni Dwiana; Cahyadi Setiawan; Dwi Atmanto; Nadiroh; I Made Astra (Jurnal Green Growth dan Manajemen Lingkungan, 2026)
The increase in domestic and industrial activities has led to a significant rise in wastewater generation, potentially causing environmental pollution if not properly treated. One of the widely developed wastewater treatment technologies is the Moving Bed Biofilm Reactor (MBBR) due to its high treatment efficiency and stable operational performance. However, this system still requires considerable energy consumption and generates residues that may contribute to environmental impacts. Therefore, this study aims to analyze the environmental impacts of an MBBR-based wastewater treatment system using the Life Cycle Assessment (LCA) approach assisted by OpenLCA software. The research employed a quantitative method with the LCA framework consisting of goal and scope definition, life cycle inventory (LCI), life cycle impact assessment (LCIA), and interpretation stages. The data included energy consumption, chemical usage, sludge production, and influent characteristics. Environmental impact analysis was conducted using the ReCiPe Midpoint (H) method. The results showed that the MBBR system achieved removal efficiencies of approximately 85% for BOD, 80% for COD, and 78% for TSS. The LCA results indicated that the largest environmental impact category was Global Warming Potential (GWP) at 0.85 kg CO₂-eq/m³, dominated by electricity consumption contributing 65% of total impacts. Statistical analysis showed that energy consumption significantly affected GWP with a significance value of 0.001. The study revealed a trade-off between treatment efficiency and increasing environmental impacts due to high energy demand. Therefore, energy optimization and environmentally friendly technologies are essential for developing sustainable MBBR systems. Keywords: Life Cycle Assessment, OpenLCA, MBBR, Global Warming Potential.